2019
DOI: 10.1111/codi.14553
|View full text |Cite
|
Sign up to set email alerts
|

European Society of Coloproctology Core Outcome Set for haemorrhoidal disease: an international Delphi study among healthcare professionals

Abstract: Aim There is considerable heterogeneity in outcomes in studies reporting on the treatment of haemorrhoidal disease (HD). The aim of this study was to develop a Core Outcome Set (COS) for HD in cooperation with the European Society of Coloproctology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…In addition, the lack of uniform outcome, measurement and reporting in HD research data hampers the ability to compare studies and the creation of optimal treatment guidelines . A Core Outcome Set was recently developed in cooperation with the ESCP .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the lack of uniform outcome, measurement and reporting in HD research data hampers the ability to compare studies and the creation of optimal treatment guidelines . A Core Outcome Set was recently developed in cooperation with the ESCP .…”
Section: Discussionmentioning
confidence: 99%
“…The recent development of a core outcome set in evaluation of haemorrhoids by van Tol et al . [24] recommended that symptom outcomes should include domains of pain, itching, soiling and blood loss. The development of the outcome set included a content validity study which established relevance and comprehensiveness through both patient and expert feedback.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome measurements we chose based on the Core Outcome Set for hemorrhoid disease developed by Breukink and colleagues and the European Society of Coloproctology may improve the quality of our research and enhance the analysis of evidence. 7 A previous research indicated that the physical appearance of the postoperative anal cushions and patients' symptoms are poorly correlated, meaning anorectal visualization is not a reliable surrogate of success. 26 Our clinical experience and principal management for hemorrhoids shows that there is no need to review colonoscopy within half a year after CAES treatment.…”
Section: Discussionmentioning
confidence: 99%
“…1,5,6 However, clinical trials investigating the effectiveness of treatments for internal hemorrhoids lack uniformity of outcome measurement, which resulted in a wide variety in outcomes between studies and a debate regarding the best treatment option for each grade of internal hemorrhoids. 7…”
Section: Introductionmentioning
confidence: 99%